Ecological Self from an Aesthetic Point of View - Hess, Gérald (The Trumpeter)

(untitled) (Athabasca University Press, 2017)
The present article develops an aesthetic signification for the idea of an ecological self proposed by Arne Næss and for its underlying relationship of identification. It is based on a discussion of a model of environmental aesthetics – the mystery model – by Stan Godlovitch. Godlovitch has presented his model as an alternative to the cognitive paradigm developed by Allen Carlson. While showing the value of this acentric aesthetic, I am proposing a different version of this model founded on a phenomenological approach – by French philosopher Maurice Merleau-Ponty. This perspective provides a better understanding of a subject's attitude of insignificance and aesthetic aloofness inherent in an acentric aesthetic experience of nature. It also shows what brings together and separates this experience, first from death, and secondly from mysticism. In so doing, it helps establish the legitimacy of the concept of the ecological self by looking at it in a new way.